2007
DOI: 10.5367/000000007780823131
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Systematic Risk in the US Restaurant Industry

Abstract: This study examines the effects of the financial ratios on systematic risk in the restaurant industry. The effects of those determinants on risk were also compared between the quick-service and full-service segments. The study used 58 publicly traded restaurant firms listed in COMPUSTAT within the category of eating and drinking places (SIC code 5812). To explain systematic risk, six financial variables were included in the study: profitability, leverage, efficiency, liquidity, growth and firm size. The most s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 15 publications
(49 reference statements)
3
37
1
Order By: Relevance
“…This study is related to Muradoglu and Sivaprasad (2012a), who reported that the relation between leverage and stock returns is not the same across industries as defined by three-digit SIC codes. We argue that the analysis of the hospitality sector is important because it is known for its reliance on external finance and leverage has been used by previous researchers to explore its predictability as a risk factor in determining performance using accounting-based measures (W. Kim et al, 2007;Shin, Hancer, Leong, & Palakurthi, 2010). Our analysis is different from theirs as we use a market-based measure of performance that is integrated into an investment strategy.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…This study is related to Muradoglu and Sivaprasad (2012a), who reported that the relation between leverage and stock returns is not the same across industries as defined by three-digit SIC codes. We argue that the analysis of the hospitality sector is important because it is known for its reliance on external finance and leverage has been used by previous researchers to explore its predictability as a risk factor in determining performance using accounting-based measures (W. Kim et al, 2007;Shin, Hancer, Leong, & Palakurthi, 2010). Our analysis is different from theirs as we use a market-based measure of performance that is integrated into an investment strategy.…”
mentioning
confidence: 97%
“…Kim et al (2002), Lee and Jang (2007), Borde (1998), Gu and Kim (2002), and W. Kim et al (2007) found leverage as a key risk factor in explaining the performance of firms in the hotel, airline, and casino industries, respectively. In this article, we investigate the relation between leverage and stock returns of all hospitality firms listed in the London Stock Exchange with operations as hotels, restaurants, pubs, travel companies, and entertainment firms.…”
Section: Research Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…It shows the ability of banks to create profits by utilizing its assets. A company with increased profitability can decrease the chance of any firm's breakdown (Kim, Ryan, & Ceschini, 2007).…”
Section: Operating Efficiency = Operating Expenses/net Salesmentioning
confidence: 99%
“…In the hospitality and tourism fi nancial literature, systematic risk studies have been centered on the restaurant industry (Borde, 1998;Gu and Kim, 2002;Kim et al, 2007), the airline industry (Lee and Jang, 2007) and the hotel Real Estate Investment Trust (REIT) industry . However, the factors affecting systematic risk have never been investigated for the hotel industry.…”
mentioning
confidence: 99%